Higher contrast thresholds for vanishing optotype recognition in macular visual fields among glaucoma patients: a structure–function analysis. Issue 11 (24th May 2021) - Wen, Yun; Chen, Zidong; Chen, Shuo; Tan, Kaixin; Kong, Yang; Cheng, Hui; Yu, Minbin
Abstract : Background/aims: We aimed to explore the impact of glaucomatous macular damage, specifically retinal ganglion cell (RGC) loss, on macular pattern vision measured by the vanishing optotype (VO) recognition contrast threshold. Methods: Seventy-two patients (mean age, 33.51±7.05 years) with primary open-angle glaucoma and 36 healthy controls (mean age, 30.25±6.70 years) were enrolled. VO recognition contrast thresholds of each participant were measured at the 16 preset test locations covering the central 5° visual field (VF). Macular sensitivity (MS) was tested by macular threshold test of Humphrey Field Analyzer. Macular RGC plus inner plexiform layer (GCIPL) thickness was also measured by spectral domain optical coherence tomography. Results: The VO contrast threshold demonstrated weak-to-moderate correlations (rho=−0.275 to −0.653) with MS (p<0.001). There was a significantly higher VO contrast threshold in glaucoma group (p<0.0001). At similar levels of MS, patients with glaucoma with GCIPL damage showed remarkably higher VO contrast thresholds than those with preserved GCIPL (p=0.0079). The structure–function relationships between VO contrast threshold and GCIPL thickness (rho=−0.725 to −0.802) were remarkably stronger than those between MS and GCIPL thickness (rho=0.210 to 0.448). VO contrast threshold showed stronger correlation with average GCIPL thickness (rho=−0.362 to −0.778) than MS (rho=0.238 to 0.398) at multiple test locations in glaucoma group. Conclusions: Glaucomatous eyes have higher contrast thresholds for VO recognition in fovea-around VF. Stronger structure–function relationships indicate that VO contrast threshold is more vulnerable to RGC damage.